Generic complexity in bachelor’s theses by Chinese English majors: an SFL perspective - Yimin Zhang,; Issra Pramoolsook, (Penerbit Universiti Kebangsaan Malaysia, 2019)
For Chinese English majors, bachelor’s theses are regarded as the most substantial piece of writing in their undergraduate study. However, in the field of EAP/ESP and genre research, thesis writing at the undergraduate level has been relatively neglected. From the perspective of genre in Systemic Functional Linguistics, the macrostructure of a bachelor’s thesis constitutes a macrogenre which combines more than one elemental genre to accomplish complex goals. An understanding of the deployment of elemental genres in this macrogenre can further help reveal the rhetorical values circulating in this thesis writing community. Based on the genre taxonomy developed by SFL genre theorists (e.g., Rose, 2010, 2015a, 2015b), this study analysed the genre deployment of 40 highly-rated bachelor’s theses written by English majors at a Chinese university, triangulated with semi-structured interviews with thesis writers and advisors. The results show that the 40 theses contained 776 shorter texts instantiating 22 types of elemental genres across 7 genre families. Specifically, reports were most extensively used by the thesis writers to transmit their received disciplinary knowledge. Arguments and text responses, though ranking lower in number, were essential to the writers’ projection of evaluative meanings and authorial selves. Stories, chronicles, explanations, and procedural genres were deployed sporadically, but empowered the writers to perform a constellation of social roles. The findings of this study may assist novice thesis writers by heightening their genre awareness, and more practically, increasing their knowledge on the specific types of elemental genres over which they need control to produce a rhetorically well-developed bachelor’s thesis. This paper then concludes with implications for teaching and researching thesis writing in non-English dominant contexts.